A pivotal phase III, randomised, placebo-controlled study of belimumab in patients with systemic lupus erythematosus located in China, Japan and South Korea. Issue 3 (2nd January 2018) - Zhang, Fengchun; Bae, Sang-Cheol; Bass, Damon; Chu, Myron; Egginton, Sally; Gordon, David; Roth, David A; Zheng, Jie; Tanaka, Yoshiya
Abstract : Background: Intravenous belimumab plus standard of care (SoC) is approved in the USA and Europe for treatment of active, autoantibody-positive systemic lupus erythematosus (SLE). Methods: This phase III, multicentre, randomised, double-blind, placebo-controlled study (BEL113750; NCT01345253 ) was conducted in 49 centres across China, Japan and South Korea (May 2011– September 2015). Patients with SLE were randomised 2:1 to intravenous belimumab 10 mg/kg or placebo, plus SoC, every 4 weeks until Week 48. The primary endpoint was the SLE Responder Index (SRI) 4 response rate at Week 52. Secondary endpoints were the percentage of patients with ≥4 point reduction in Safety of Oestrogens in Lupus Erythematosus National Assessment-SLE Disease Activity Index (SELENA-SLEDAI), SRI7, time to first severe flare and number of days prednisone (or equivalent) dose ≤7.5 mg/day and/or reduced by 50% from baseline. Safety was assessed. Results: The modified intent-to-treat population included 677 patients (belimumab n=451, placebo n=226). At Week 52, the SRI4 response rate was higher with belimumab versus placebo (53.8% vs 40.1%; OR: 1.99 (95% CI: 1.40, 2.82; P=0.0001)). The percentages of patients with a ≥4 point reduction in SELENA-SLEDAI and an SRI7 response were significantly greater for belimumab versus placebo. Patients in the belimumab group had a 50% lower risk of experiencing a severe flare than those receiving placebo (P=0.0004). In patients with baseline prednisone dose >7.5 mg/day, there was a significant reduction in steroid use favouring belimumab (P=0.0228). The incidence of adverse events was similar between groups. Conclusions: In patients with SLE from North East Asia, belimumab significantly improved disease activity, while reducing prednisone use, with no new safety issues.